An In Vitro Fermentation Study on the Effects of Gluten FriendlyTM Bread on Microbiota and Short Chain Fatty Acids of Fecal Samples from Healthy and Celiac Subjects - Costabile, Adele; Bergillos-Meca, Triana; Landriscina, Loretta; Bevilacqua, Antonio; Gonzalez-Salvador, Isidro; Corbo, Maria R.; Petruzzi, Leonardo; Sinigaglia, Milena; Lamacchia, Carmela (Frontiers in Microbiology, 2017)
Recently, an innovative gluten detoxification method called Gluten FriendlyTM (GF) has been developed. It induces structural modifications, which abolish the antigenic capacity of gluten and reduce the in vitro immunogenicity of the most common epitopes involved in coeliac disease, without compromising the nutritional and technological properties. This study investigated the in vitro effects of GF bread (GFB) on the faecal microbiota from healthy and coeliac individuals by a three-stage continuous fermentative system, which simulates the colon (vessel 1, proximal colon; vessel 2, transverse colon; vessel 3, distal colon), as well as on the production of short chain fatty acids (SCFA, acetate, propionate, butyrate). The system was fed with GFB and the changes in microbiota through fluorescence in situ hybridization (FISH) and in SCFA content were assessed. GFB exerted beneficial modulations such as bifidogenic effects in each compartment of the model both with healthy and coeliac derived samples, as well as growth in Clostridium clusters XIVa+b in coeliac derived samples. Furthermore, increased levels of acetic acid were found in vessel 1 inoculated with the faecal microbiota of healthy individuals, as well as acetic and propionic in vessel 1 and 2 with coeliac derived samples. In addition, the use of multivariate approaches showed that the supplementation of GFB could result in a different modulation of the faecal microbiota and SCFA, as a function of initial equilibrium.